"Seesaw balloon-wire cutting" technique is superior to Tornus catheter in balloon uncrossable chronic total occlusions. (1st February 2017) - Xue, Jingyi; Li, Jianqiang; Wang, Hongjun; Sheng, Li; Gong, Yongtai; Sun, Danghui; Li, Shuang; Li, Weimin; Wang, Dingyu; Li, Yue
Abstract: Background: Inability to advance a balloon is a well-recognized cause leading to a failure in recanalization of chronic total occlusions (CTOs) despite successfully passing a guidewire. A few techniques and devices have been introduced to facilitate balloon passage, especially the use of Tornus catheter. However, complex manipulation, expensive cost, and availability limit the application of these methods. This study was to evaluate the efficiency and safety of "seesaw balloon-wire cutting" technique in comparison with Tornus catheter for balloon uncrossable CTOs. Methods: Eighty patients with balloon uncrossable CTOs were enrolled in this study. Among them, 40 patients treated with "seesaw balloon-wire cutting" technique were consecutively investigated and 40 patients treated with Tornus catheter before were matched retrospectively. A rotablator or retrograde strategy was taken as a bail-out strategy. Success rates of device and procedure and complication rate were assessed. Complications included coronary dissection, cardiac tamponade, death, Q-wave myocardial infarction (MI), non-Q-wave MI, emergency PCI and bypass surgery. Results: Compared with the Tornus catheter, device success rate was significantly higher with the "seesaw balloon-wire cutting" technique (87.5% vs. 45.0%, P < 0.001), and the mean procedural time was much shorter (90.5 ± 8.3 min vs. 141.5 ± 21.3 min, P < 0.001). The procedural success rate was also higher with the "seesaw balloon-wire cutting" technique (92.5% vs.72.5%, P = 0.037). There were no differences in complication rate. Conclusion: The "seesaw balloon-wire cutting" technique is superior to the Tornus catheter in treating balloon uncrossable CTOs.